STATUS OF “KUAKATA” A NEGLECTED NATURAL SCENIC RESOURCE OF BANGLADESH - Rahman, Md. Mahfjur; Rahman, Md. Atiqur; Nahar, Azizun (European Scientific Journal, ESJ, 2015)
There are many years since we have independent from the foreign ruling. But we are now in the least developed country because of lacking of the integration and inter-coordination among the different political, economical and social sectors. Though we are in the loaded position with the vast population, it would be the most resourceful by the proper nourishment and proper adoption with education, knowledge and training for the sustainable utilization of the God- gifted enormous natural resources. Kuakata the second largest Sea-beach is another one of the natural scenic resource of our country which is still now under negligence and mismanagement including its demographic development. By the proper planning and inter-sectoral coordination Kuakata can be turned into a most effective and largest economical source of the national revenue and common people livelihood. There has been tried to present the present demographic, educational, Hospitalization, transportation, present and potential resources and other tourism facilities in this study. Here is tried to highlight what have in this tourism place and what are to be needed in kuakata.